Effects of Ce addition on the Cu-Mg-Fe alloy hot deformation behavior. (September 2018) - Wang, Bingjie; Zhang, Yi; Tian, Baohong; An, Junchao; Volinsky, Alex A.; Sun, Huili; Liu, Yong; Song, Kexing
Abstract: The effects of Ce addition on the Cu-Mg-Fe alloy hot deformation process were investigated through the isothermal compression tests using the Gleeble-1500D thermo-mechanical simulator at 500–850 °C temperature range and 0.001–10 s −1 strain rate range. The interaction of work hardening, dynamic recovery and dynamic recrystallization during plastic deformation was studied, and the constitutive equations of Cu-Mg-Fe and Cu-Mg-Fe-Ce alloys were established. The addition of Ce can delay the occurrence of dynamic recrystallization, enhance the flow stress and apparently narrow the unstable domain during hot deformation process of the Cu-Mg-Fe alloy. Two optimal hot working parameters for the Cu-Mg-Fe alloy are obtained. The first is temperature of 650–800 °C and strain rate of 0.001–0.01 s −1, and the second is temperature of 775–850 °C and strain rate of 0.01–0.6 s −1 . The optimal hot working parameters for the Cu-Mg-Fe-Ce alloy are 675–850 °C and strain rate of 0.01–0.4 s −1 . The precipitate of the Cu-Mg-Fe-Ce alloy deformed at 850 °C and 0.001 s −1 was determined to be CuMg2. CuMg2 precipitation can improve the hardness and hot deformation activation energy of the Cu-Mg-Fe alloy. Meanwhile, the addition of Ce can promote the precipitation of CuMg2 . Highlights: Effects of Ce addition on the Cu-Mg-Fe alloy hot deformation behavior were investigated. . The addition of Ce can delay the occurrence of dynamic recrystallization. . The activation energy of Cu-Mg-Fe and Cu-Mg-Fe-Ce alloys are 255.3 kJ/mol and 323.7 kJ/mol, respectively. . Dislocation slip and twinning contribute to the dynamic recrystallization mechanism.